A Pre- and Postoperative Evaluation of Multiple Joint Involvement as the Initial Finding of Cervical Syringomyelia and Neuropathic Arthropathy - Ayşin KISABAY; Sinem ZEYBEK; Serpil SARI; Aliye TANYELİ and Deniz SELÇUKİ1 (Archives of Rheumatology, 2013)
Syringomyelia is a progressive, degenerative disorder, in which a longitudinal cyst forms within the spinal cord. Neuropathic arthropathy can be seen in the late phases of the disease, with the most frequent involvement being in the shoulder. Herein, we present a 42-year-old female case who was diagnosed with syringomyelia as well as Arnold-Chiari Syndrome and neuropathic arthropathy. Her initial complaints were painless edema in the right shoulder and elbow, wounds on the tips of her fingers and amputations. She was evaluated both pre- and postoperative periods. It should be kept in mind that neuropathic arthropathy may develop as the initial symptom in spinal cord lesions which progress slowly.